Outcome measurement in psychiatry research - Rodrigues, Myanca Deanne (My University, 2024)
Background: Outcomes are integral to psychiatry research for evaluating intervention effectiveness in randomized controlled trials (RCTs) and understanding disease progression in observational research. Carefully defined, measured, and consistently used outcomes guide clinical decision-making and enhance research applicability. Bridging methodological gaps through rigorous assessment is essential for minimizing variability and mitigating research waste. Objectives: This dissertation aims to assess: (i) outcome selection in geriatric depression RCTs, (ii) primary outcome reporting in these trials, and (iii) measurement of multimorbidity patterns in observational research on people with opioid use disorder (OUD). Methods: Three studies were conducted: (i) a systematic survey examining outcome selection heterogeneity in geriatric depression RCTs (2011-2021), (ii) an assessment of primary outcome reporting comprehensiveness in these trials, and (iii) an observational study using hierarchical cluster analysis (HCA) and K-means clustering to compare statistical techniques for measuring multimorbidity patterns among people with OUD. Results: Findings suggest variability in outcome selection, reporting, and measurement in psychiatry research. (i) The systematic survey revealed significant heterogeneity in outcomes and outcome measurement instruments (OMIs) in geriatric depression RCTs, impeding cross-study comparisons. (ii) The assessment of primary outcome reporting highlighted variability and insufficiency in reporting the rationale for outcome selection, measurement properties of OMIs, and criteria for clinically meaningful change, limiting the interpretability of trial findings. (iii) The observational study on multimorbidity patterns among people with OUD identified significant variations in chronic condition clusters using HCA and K-means clustering, indicating the need for careful consideration of statistical techniques in outcome measurement to inform clinical care accurately. Conclusion: These findings highlight the need for standardized practices in outcome selection, reporting, and measurement in psychiatry research. Addressing these issues through developing core outcome sets, improving adherence to reporting guidelines, and refining measurement methodologies will enhance research reliability and applicability, ultimately improving clinical decision-making and patient care in psychiatry.
Methodological and statistical assessment of the selection, reporting, and measurement of outcomes in psychiatry research
Keywords: Mental health; Outcome measurement; Geriatric depression; Psychiatry research; Clinical trials; Opioid use disorder